L’écriture collective du code source informatique - Stéphane Couture (Revue d'anthropologie des connaissances)
This article analyzes the collective writing of software source code. Software source code is a set of textual documents that formally specify the behavior of software – its script. The article draws on work in the sociology of science and technology and in the anthropology of writing, which insist on the (sometimes invisible) work that is necessary to the stability and vivacity of written artifacts and information infrastructures. We analyze the ways in which different versions of software source code are managed, and focus particularly on the computer act of “committing”. We insist on issues of visibility related to the act of committing, issues that are taking a growing importance as an indicator of one’s contribution in the information society.